Численное моделирование процесса перемешивания взаиморастворимых жидкостей в роторно-пульсационном аппарате - Басок, Б.И.; Давыденко, Б.В.; Ободович, А.Н.; Пироженко, И.А. (Видавничий дім "Академперіодика" НАН України, 2007)
Rotor-pulse apparatus are successfully used for the creation of homogeneous mixtures from high-viscosity components. The fields of concentration of components are defined as a result of the numerical simulation of the liquid flow and the process of mass transfer in the working space of an apparatus. The time dependence of the average concentrations in the input and output sections of the working space is investigated. The estimation of the efficiency of a rotor-pulse apparatus as a mixing device is made on the basis of the proposed criterion.